2013
DOI: 10.1080/13670050.2013.836806
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism in schools and society: language, identity, and policy

Abstract: Bilingualism has permeated people's life in our current globalized world. However, as Shin aptly points out in this book, there are still major misconceptions of bilingualism arising from the traditional monolingual ideology. To overcome this, bilingualism should be understood as a phenomenon in its own right. Shin presents state-of-the-art knowledge of this issue by reviewing and discussing up-to-date empirical research from two overarching aspects -the social and educational needs of bilingual/multilingual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For example, bilingualism has been considered as a unique cultural asset for Mexican American children (Borrero, 2015). As bilingualism is associated with better academic outcomes in general (Golash‐Boza, 2005; Ke, 2014), future studies can explore whether such benefits still hold for Mexican American adolescent brokers and whether such benefits can counteract the negative influences of discrimination on adolescents' academic outcomes. In addition, the three indicators of academic competence (i.e., grades, learning goals and school engagement) in the current studies were self‐reported by adolescents, which may introduce self‐evaluation biases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bilingualism has been considered as a unique cultural asset for Mexican American children (Borrero, 2015). As bilingualism is associated with better academic outcomes in general (Golash‐Boza, 2005; Ke, 2014), future studies can explore whether such benefits still hold for Mexican American adolescent brokers and whether such benefits can counteract the negative influences of discrimination on adolescents' academic outcomes. In addition, the three indicators of academic competence (i.e., grades, learning goals and school engagement) in the current studies were self‐reported by adolescents, which may introduce self‐evaluation biases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, García Coll et al’s (1996) integrative model posits that such an adaptive acculturative strategy can promote children’s developmental competence. Prior studies have found that bilingualism is related to positive academic outcomes, as bilingual children have higher test scores (Golash-Boza, 2005) and lower high school drop-out rates (Ke, 2014) compared with their monolingual counterparts. Therefore, it is essential to consider the benefits of bilingualism in light of the academic risks faced by Mexican-origin adolescents.…”
Section: Bilingualism and Academic Competence Among Mexican-origin Ad...mentioning
confidence: 99%
“…Thus, we expect the emergence of a group characterized by high proficiency in both English and Spanish, with positive brokering experiences. Membership in this group would be most optimal for bilingual adolescents’ sense of academic competence, given prior evidence demonstrating the beneficial effects of bilingualism and positive brokering experiences on adolescent adjustment (Acoach & Webb, 2004; Ke, 2014).…”
Section: Bilingual Language Broker Profiles Reflecting the Tripartite...mentioning
confidence: 99%